The Hubungan Tingkat Paternal Postpartum Depression (PPD) Terhadap Risiko Perilaku Kekerasan Pada Anak Di Wilayah Kerja Puskesmas Pulo Lor, Kabupaten Jombang: Hubungan Tingkat Paternal Postpartum Depression (PPD) Terhadap Risiko Perilaku Kekerasan Pada Anak Di Wilayah Kerja Puskesmas Pulo Lor, Kabupaten Jombang - Ekawati, Dessy; Azmi, Nurul (WELL BEING, 2023)
People often think that only mothers can experience postpartum depression. However, in fact, many fathers experience postpartum depression and it is not handled well because fathers are often silent and prioritize the welfare of the family. This results in suppressed emotions and the risk of violent behavior in children. This study aims to analyze the relationship between the level of paternal postpartum depression and the risk of violent behavior in children in the Pulo Lor Public Health Center working area, Jombang Regency. This research is a correlational analytical research using the cross sectional method. The total sampling technique was used in this research using 150 respondents with the characteristics of a father aged 15 - 30 years who had just had their first child or second child within a year of the couple's postpartum period. Data analysis in this study used the Spearman's rho statistical test, resulting in r = 0.010. The results of this study show that there is a relationship between the level of paternal postpartum depression and the risk of violent behavior in children in the work area of the Jombang district health center.